2022
DOI: 10.2147/ijgm.s344863
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recurrent Pancreatitis After First Episode of Acute Pancreatitis

Abstract: In recent years, the cure rate of acute pancreatitis (AP) has increased gradually, but the morbidity of recurrent acute pancreatitis (RAP) has not decreased. Patients with RAP have a poor quality of life and are more likely to develop into chronic pancreatitis. To investigate the risk factors of RAP after first pancreatitis attack is very necessary. Methods: Patients with first episode AP admitted to Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine from January 2018 to May 2021 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…AP recurrence was not found to be linked to T2DM in our cohort, similar to the result of another study [ 24 ]. However, we believe that this result should be validated through future prospective studies as our study was a retrospective one with limitations due to its design.…”
Section: Discussionsupporting
confidence: 92%
“…AP recurrence was not found to be linked to T2DM in our cohort, similar to the result of another study [ 24 ]. However, we believe that this result should be validated through future prospective studies as our study was a retrospective one with limitations due to its design.…”
Section: Discussionsupporting
confidence: 92%
“…After reviewing the full text of the remaining 66 articles, 24 more articles were excluded (22 articles included patients who had more than one previous episodes of pancreatitis; two studies included the same population as one of the eligible studies). Consequently, 42 studies 8,9,14–53 (32 retrospective cohort, 8 prospective cohort, and 2 randomized controlled trials) including a total of 57 815 patients were eligible for inclusion. The study flow chart is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…), and clinical characteristics (like etiology, local complications, etc.) (43)(44)(45). Chen et al (17) first showed that the radiomics model based on CECT exhibits promising value in the early prediction of RAP.…”
Section: Clinical Applications Predicting Recurrent Acute Pancreatitismentioning
confidence: 99%